How do gender and competition level influence the physical demands in worst-case scenarios of elite football referees? - Gemma Martinez-Torremocha; Antonio Alonso-Callejo; Javier Sanchez-Sanchez; Jorge Garcia-Unanue; Leonor Gallardo; Maria Luisa Martin-Sanchez; Carlos Serrano; Jose Luis Felipe (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The aim of this study was to describe and compare the physical demands in Worst-Case Scenarios (WCS) across different competition levels in male and female football of Spanish elite football referees during matches, comparing competitions independently for male and female referees. Methods Physical demands (total distance [TD], total distance > 18 km/h [TD18], total distance > 21 km/h [TD21], total distance > 24 km/h [TD24], accelerations (> 3 m/s2) [Acc] and decelerations (<-3 m/s2) [Dec]) were recorded over different time windows (0.5, 1, 3, 5 and 10 min) on 24 professional male Spanish football referees from male 1st Division, 26 from male 2nd Division and 24 professional female Spanish football referees from female 1st Division during the 2020/21, 2021/22, and 2022/23 seasons over a total of 2,156 official matches, using Global Positioning Systems. Results Results showed that male referees experienced higher physical demands, particularly during the shortest time windows of WCS (0.5 and 1 min), where the highest relative physical loads were observed. Significant differences (p < 0.05) were found between competitions, with higher demands recorded in the 2nd Division and Champions League. In contrast, female referees faced their greatest physical demands in national competitions, such as the Queen’s Cup, compared to international competitions. Both genders demonstrated higher intensity during shorter time windows, highlighting the need to be prepared for short and high-intensity match periods. Conclusions The study concludes that physical demands vary according to gender and level of competition. Male referees face higher workloads, and female referees have different demands depending on the competitive context. These findings highlight the need for tailored training programs and recovery strategies to address the specific demands of referees across different match contexts. For male referees, training should emphasize short-duration, high-intensity efforts, especially for competitions such as the Second Division and Champions League. For female referees, programs should replicate the demands observed in national competitions like the Queen’s Cup. These adaptations can improve performance, reduce injury risk, and enhance match officiating quality. Clinical trial number not applicable.